STUDY OF MAGNETIC HARDENING IN Sm(Co1-xCux)5 ALLOY - Awan, M. S.; Bhatti, A. S.; Farooque, M. (The Nucleus, 2020)
Magnetic hardening has been examined in the samarium (Sm), cobalt (Co) and copper (Cu) fused permanent magnets by correlating the magnetic properties with annealing temperature and microstructure of the samples. For the Sm(Co1-xCux)5 system, with various copper contents (x= 0, 0.2, 0.3, 0.4 and 0.5) the shape of initial magnetization curve indicated that the magnetic hardening process involved in these types of magnets consists of domain wall pinning type. This is consistent with the microstructure studies which show the existence of nonmagnetic Cu-rich precipitates in the Co-rich matrix. Copper substituted samples were annealed in the temperature range (300 – 1000) oC for 3h under the protective atmosphere of argon (Ar) gas. Both cast and annealed samples prepared by tri-arc melting technique exhibit two-phase microstructure responsible for enhanced magnetic properties. Metallographic and surface studies were carried out using a digital optical microscope (OM). X-ray diffraction (XRD) studies confirmed that the alloys solidefied in the hexagonal crystal structure. The lattice parameters and unit cell volume increase with increasing Cu content. Scanning electron microscope (SEM) coupled with energy dispersive X-ray (EDX) was used to examine the surface morphology, compositional variations, elemental segregations, formation and effect of annealing on the different phases. Later these parameters were related to the magnetic properties. Copper-rich phase precipitates in the Co- rich matrix may serves as the pinning centers for the domain wall motion. Introduction of these pinning centers improved the magnetic hardening of the alloy. Annealing the Cu-substituted alloy further improved the magnetic properties. During annealing, diffusion of copper played the key role for enhanced magnetic properties. It was found that both Cu substitution and subsequant annealing are the dominating factors determining the magnetic properties of these magnetic alloys.